Effectiveness of two methods for stunning pigs: electrical stunning head-heart and CO2 stunning - Acevedo-Giraldo, Juan David (2017)
The aims of this study were to evaluate and compare the effectiveness of the electrical stunning head-heart (MA1) and CO2 stunning (MA2), and to assess the infrastructure and management of pigs in two commercial slaughterhouses in Colombia. A crosssectional study that evaluated 520 pigs (MA1=185 and MA2=335) was performed. Behavioral indicators in the stunning box and consciousness indicators before and after bleeding were evaluated. Eye movements (39%) and spontaneous eye blinking (36.7%) were common in MA1, while rhythmic breathing (24.1%) was evident in MA2. The effectiveness of stunning was low in the two slaughterhouses before (48.7%, 50.5%) and after bleeding (79.5%, 37.3%). It is recommended to establish indicators to routinely assess the effectiveness of stunning, and a programme of preventive maintenance of equipment and continuous training of staff.